2022
DOI: 10.7759/cureus.29406
|View full text |Cite
|
Sign up to set email alerts
|

Hernia Causing Ureteral Obstruction With Hydronephrosis and Subsequent Urinary Tract Infection and Sepsis

Abstract: Inguinal hernias are common anatomic defects, especially among men. Complications of inguinal hernias include incarceration, but incarcerated hernias rarely cause other disturbances. An 86-year-old man with a history of chronic kidney disease (stage IIIb) presented with recurrent urinary tract infections and acute kidney injury with sepsis. Physical examination revealed a right inguinal hernia, and non-contrast abdominal computed tomography revealed right ureteral obstruction and distal entrapment by the ingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Our study also revealed a significantly increased burden of inguinal hernia among the cases, which is consistent with existing literature that suggests inguinal hernia is the predominant type of abdominal wall hernia [20]. The increased occurrence of inguinal hernia is ascribed to the altered architecture of the abdominal wall in humans, which may have resulted from evolutionary changes [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study also revealed a significantly increased burden of inguinal hernia among the cases, which is consistent with existing literature that suggests inguinal hernia is the predominant type of abdominal wall hernia [20]. The increased occurrence of inguinal hernia is ascribed to the altered architecture of the abdominal wall in humans, which may have resulted from evolutionary changes [21].…”
Section: Discussionsupporting
confidence: 90%
“…The RDW provides information on erythrocyte anisocytosis, and its elevation suggests an impaired synthesis of erythrocytes, which may be observed in haemoglobinopathies and some nutritional deficiencies (like iron-, cobalamin-, or folate deficiency), increased haemolysis, or following haemotransfusion [28]. Also, the variation in the size of erythrocytes could be due to pro-inflammatory cytokines that impede the maturation of erythrocytes by erythropoietin [8,20]. The suggested anisocytosis, therefore, may have resulted from the inflammation-mediated discharge of the immature erythrocytes into circulation [14].…”
Section: Discussionmentioning
confidence: 99%
“…We report an unusual case of a pre-existing inguinal ureteric hernia that developed obstruction and superimposed pyelonephritis. We have identified just 2 cases in the literature of urosepsis secondary to native ureteroinguinal hernia-related obstruction [11 , 14] .…”
Section: Discussionmentioning
confidence: 99%
“…Common complications of a hernia requiring surgery include incarceration, bowel obstruction, and strangulation [ 1 ]. However, an inguinal hernia containing a ureter is an uncommon clinical entity and usually is asymptomatic [ 2 ]. Ureteral hernias were first reported in the nineteenth century, but since then only about 150 cases have been reported in the literature [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the ureter is entrapped, manifestations can include flank pain, recurrent urinary tract infections, or chronic renal damage because of ureteral obstruction. In cases of prolonged entrapment, hydronephrosis and even sepsis may occur [ 2 ].…”
Section: Introductionmentioning
confidence: 99%